A Review of The Models of Land Development Process: The Equilibrium and Event-Sequence Model - Ismail, Maziah (Fakulti Ukur dan Harta Tanah, 1996)
This paper is the first part of a three series paper that provides a comprehensive review of the existing models of land development process. In each of the papers the characteristics of these models are presented and evaluated critically in relation to their clarity, applicability and theoretical underpinnings. This will bring together from various sources the principal approaches in the analysis of development activity and also provides a platform to discuss the key components and the implication of the process. Most importantly the review provides some guidelines for the rejection and adoption of a particular methodology as a basis for undertaking research. In this first paper, it is suggested that the equilibrium models, which are based on the neo-classical parameters of demand and supply, in terms of undertaking research are set-up at a level of abstraction. The problem is that it is difficult to substantiate precisely between the actual investigate events and the affecting structural forces. On the other hand, although the event-sequence models focus on the potential blockages to develop activity, they lack the specification of actors and interests, and so provide little help in explaining why a development process takes the form that it does in a particular case.